Unpacking Property: Media, Ownership, and Power in Transformation| Media Property: New Explorations in Media and Communication Studies—Introduction - Sebastian Sevignani; Hendrik Theine (International Journal of Communication, 2025)
This Special Section explores the concept of property as a central theme in media and communication studies, emphasizing its role as a social institution that regulates power, access, and rights in relation to media and communication assets. Despite property being fundamental to capitalist societies, its analysis within the field has often been limited to specific subfields such as political economy, media sociology, and media industry studies. Building on existing categorizations, this Special Section connects property in the media to contemporary societal and economic transformations, examines diverse media ownership structures and their implications for public interest, and analyzes the discursive construction and legitimization of property and wealth in media narratives. By addressing key developments such as media concentration, feminist political economy perspectives, and the monopolization of global internet corporations, this issue broadens the scope of property research in communication studies and highlights its relevance across the discipline.